Prevalence of Non-Communicable disease in Geriatrics population of Kalaburagi District: A Cross-sectional Study in Urban Field Practice Area. (Indian Journal of Public Health Research & Development, 2024)
Context/Background:Worldwide total population of geriatric was 703 million (9%) in year 2019 according to United Nation report. The geriatric population is estimated to increase to 198 million by 2030 in India. With advancing years, the incidence of communicable and non-communicable disease (NCD) increases. Most of the available studies on morbidity in India are disease specific and fail to provide comprehensive knowledge about NCD.Aims/Objectives:• To estimate prevalence of non-communicable disease (NCD) in elderly.• To assess the risk factor associated with non-communicable disease.Methodology:A community based cross-sectional study was conducted among geriatric people in urban areas of Kalaburagi district, Karnataka. Study participants consisted of age ≥60 years were comprised in the study and a sample size of 185 was calculated.Pre-designed, pre-tested and semi-structured questionnaire was used to collect information on risk factor and morbidity status of study participants.Data was computed in excel sheets Microsoft 2013 and using SPSS version 25.0 for utilizing appropriate statistical method to calculate frequency and percentage.Results:Hypertension is the most prevalent morbidity NCD in the urban elderly population 26.49% of Kalaburagi CHC Rajapur. Then followed by diabetes 7.57% and myocardial infraction 1.62%. Chewing and Smoking tobacco found to be having significant association in disease causation in elderly population.Conclusions:Prevalence of NCD like Hypertension, Diabetes, MI etc can be prevented by reduction of the high-risk factor such as Life style changes, Diet Modification, Changing Habits of alcohol and tobacco.
Keywords: Urban population, non-communicable diseases, elderly Morbidity, NCD Risk factor.